Stingles Bee Propolis Extract as An Active Ingredient in Antibacterial Ointment Formula - Arrijal, Nail Zufar; Fauziyyah, Fadhilah Fida; Sugiarto, Eko; Hayati, Septi Nur; Rizal, Wahyu Anggo (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2025)
Stingless bees, also known as kelulut or klanceng (in local languages), are now widely cultivated in Indonesia. Stingless bees produce honey and propolis, which is the residue from honey extraction and is more abundant than honey itself. In this study, the processing of honey sacs or propolis into active ingredients for antibacterial ointments was optimized, specifically to address skin diseases caused by the bacteria Staphylococcus aureus and Streptococcus mutans. Propolis was extracted using aqua dest and 96% ethanol and optimized using three methods, namely sonication, maceration, and decoction, and antibacterial testing was carried out on S. aureus and S. mutans test bacteria. Antibacterial testing was carried out on the extracts using the diffusion method and the microdilution method. The results of the testing showed that propolis extract was most effectively extracted with water solvent, which had a bacterial inhibition concentration of 1,000–8,000 μg/mL. Water-based propolis extract can be used as a raw material for antibacterial ointments with a usage concentration of 5–15% and has been proven effective in inhibiting bacterial growth as observed using a Scanning Electron Microscope (SEM).